Improving the Efficiency of Aviation Products Design Based on International Standards and Robust Approaches. (January 2019) - Dmitriev, A; Mitroshkina, T
Abstract: The article considers the possibility of using QFD, robust design and other modern approaches for designing innovative aviation products. As an example, the projected unmanned aerial vehicle and engine, as its key part, are considered. Based on expert evaluation and analysis of benchmarking data, the main consumer requirements for UAV and a small-size gas turbine engine were identified. It is also necessary to pay attention to such general requirements as low noise, low emission of harmful substances (CO and NOx). The use of international standards of the ISO 16355 series as a methodology and basis for improving design efficiency is discussed. The results and conclusions can be applied to various types of aviation products, as well as used in other industries.